Magneto‐Endosomalytic Therapy for Cancer. Issue 9 (6th August 2021) - Zhao, Pengfei; Han, Yan; Nguyen, Holly; Corey, Eva; Gao, Xiaohu
Abstract: A remarkably simple yet effective mode of cancer treatment is reported by repurposing clinically approved magnetic nanoparticles (MNPs). Intracellular nanoparticle self‐assembly directed by static parallel magnetic fields leads to cell death in targeted tissues while leaving other cells and organs intact. This simple concept opens a new avenue to treat cancer, capitalizing on nanosciences and the nanoparticle (NP) design principles accumulated in the past decades. Abstract : Magneto‐endosomalytic therapy (MELT) for cancer repurposes clinically approved magnetic nanoparticles (MNPs) for medical imaging and iron‐deficiency treatment to general cancer therapy. Inside a static parallel magnetic field, particle self‐assembly converts biocompatible MNPs into lethal machinery for cancer. This new strategy is remarkably simple yet effective, providing a new avenue toward nanotechnology clinical translation.